Determination of Location and Design of Trans Palu Bus Stops (Case Study: Corridor 1 and Corridor 3) - Agus Adijaya Pratama; Taslim Bahar; Novita Pradani (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Corridors 1 and 3 of the Trans Palu Bus system currently lack bus stops as supporting facilities, and many passenger pick-up/drop-off points are still not served by bus stops or shelters. This study aims to examine the existing conditions of bus stop locations, determine the number of bus stops needed, and identify suitable locations and designs for bus stops along Corridors 1 and 3 of the Trans Palu Bus. Based on a survey conducted by the researcher, the average walking distance preferred by 600 respondents is 200 meters. The bus stop demand was analyzed using a buffer analysis method to assess land use potential along the corridors. The number of bus stops needed for each segment was then calculated based on a stop-to-stop distance of 400 meters, aligning with the respondents' walking distance preference. The selection of bus stop locations also refers to the categorization of public transport stop types (Directorate of Land Transport, 1996). According to the analysis results, the existing condition of Corridor 1 includes 32 bus stopping points, consisting of 23 bus stop signs, 1 permanent shelter (Pegadaian Shelter), and 8 points with no supporting facilities. Corridor 3M has 15 bus stopping points, including 9 bus stop signs and 6 points with no facilities. Corridor 3Y has 21 stopping points, consisting of 9 bus stop signs, 1 permanent shelter (Gatot Subroto Shelter), and 11 points with no facilities. Based on the analysis, the number of bus stops needed is 84 for Corridor 1, 30 for Corridor 3M, and 39 for Corridor 3Y.